Diversity of Arbuscular Mycorrhizal Fungi at Kelicung Stands (Diospyros macrophylla Blume) In KHDTK Rarung, Central Lombok - Utami, Desty Sasana Putri; Mansur, Irdika; Hilwan, Iwan; Haryantini, Baiq Azizah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Kelicung tree (Diospyros macrophylla) is a native tree species of West Nusa Tenggara. It is a slow-growing tree with very good wood ornament, strength, and durability properties. Symbiotic mutualism between kelicung and mycorrhiza has not been documented. Mycrorrhiza is a mutualism symbiosis between fungi and plant roots that could improve plant growth due to increase nutrient and water absorbtion. Therefore, the objective of this study is to investigate mycorrhizal symbiosis in kelicung roots. Soil and root samples were taken in the Rarung Special Purpose Forest Area at 0 – 20 cm depth. Isolation and identification of arbuscular mycorrhizal fungi used screening and centrifugation methods to identify spore density, diversity, abundance, and frequency. Furthermore, root staining and colonization of arbuscular mycorrhizal fungi were carried out by observing the structure of vesicles, arbuscules, hyphae, and spores on Kelicung roots. The research results showed that the average number of spores found was 846 spores/50 g of soil. Spores were identified in two genera: Glomus sp and Acaulospora sp. Glomus spores found were round, the colour of the spores was yellow, the spores did not react when Melzer's solution was dropped, and the spore walls of the Arbuscular mycorrhizal fungi of the genus Glomus consisted of 1-2 layers of cell walls. Observation of root colonization, no structures of root arbuscular mycorrhizal fungi were found in Kelicung. Keywords: Acaulospora sp., Arbuscular mycorrhizal fungi, Diospyros macrophylla, Glomus sp., Kelicung